Health disparities influence peripheral venous access insertion time in the emergency department: An observational study - Charlotte O’Sullivan; Nicholas Mielke; Yuying Xing; Amit Bahl (PLoS ONE, 2025)
Objective This retrospective, multicenter study aimed to investigate disparities in peripheral intravenous catheter (PIVC) placement wait times among patients in emergency departments (EDs), focusing on the impact of factors such as race, sex, age, and comorbidities. Methods Electronical health record (EHR) data from four EDs within Corewell Health System were analyzed for adult patients who underwent PIVC placement between January 1st, 2021 and January 31st, 2023. Multivariable linear regression models were employed to analyze associations between patient demographics (including race, sex, age, and comorbidities) and PIVC placement wait times. Adjustments were made for Charlson comorbidity index, emergency severity index, hospital size, obesity, and method of PIVC insertion. Results Among 319,938 PIVC placements analyzed, significant disparities were observed: Black patients waited 9.65% longer for PIVC placement compared to White patients (p < 0.001). Women experienced a 6.67% longer wait time than men (p < 0.001). Obese and elderly patients also experienced prolonged wait times. These disparities persisted across both ultrasound-guided and traditionally placed PIVCs. Conclusions This study underscores substantial disparities in PIVC placement wait times in EDs, influenced by race, sex, age, and comorbidities. Addressing these disparities is crucial for improving equity in emergency care delivery. Future research should focus on implementing targeted interventions to mitigate these disparities and enhance timely access to essential medical interventions for all patient populations.